2021
DOI: 10.3389/fcell.2021.718962
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Transmission of Human OGG1 Protects Mice Against Genetically- and Diet-Induced Obesity Through Increased Tissue Mitochondrial Content

Abstract: Obesity and related metabolic disorders are pressing public health concerns, raising the risk for a multitude of chronic diseases. Obesity is multi-factorial disease, with both diet and lifestyle, as well as genetic and developmental factors leading to alterations in energy balance. In this regard, a novel role for DNA repair glycosylases in modulating risk for obesity has been previously established. Global deletion of either of two different glycosylases with varying substrate specificities, Nei-like endonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…Energy expenditure was measured by indirect calorimetry (Oxymax, Columbus Instruments, Columbus, OH) after 8 weeks of feeding, as previously described ( 41 ). Briefly, oxygen consumption (VO 2 ) and carbon dioxide production (VCO 2 ) were determined in individually housed animals with ad libitum access to HFD and water; both DHF and Abx were maintained in drinking water of respective groups during the calorimetry studies.…”
Section: Methodsmentioning
confidence: 99%
“…Energy expenditure was measured by indirect calorimetry (Oxymax, Columbus Instruments, Columbus, OH) after 8 weeks of feeding, as previously described ( 41 ). Briefly, oxygen consumption (VO 2 ) and carbon dioxide production (VCO 2 ) were determined in individually housed animals with ad libitum access to HFD and water; both DHF and Abx were maintained in drinking water of respective groups during the calorimetry studies.…”
Section: Methodsmentioning
confidence: 99%
“…Since data from both the Ogg1 −/− and Neil1 −/− mouse models indicated that BERmediated repair in mitochondria likely plays an integral role in regulating energy balance, we hypothesized that in contrast to decreased repair levels, increased expression of a mitochondrial-targeted human OGG1 might render mice more resistant to obesity and metabolic syndrome [121][122][123]. These studies utilized a transgenic OGG1 model (OGG1 Tg ) developed in the lab of Dr. Lars Eide, in which OGG1 Tg mice constitutively expressed the human OGG1a gene coupled with the mitochondrial targeting sequence of the manganese superoxide dismutase gene.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…While all of the above studies utilized a high-fat diet to accelerate the manifestations of metabolic syndrome, yellow Agouti mice (A y /α) represent a genetic model of obesity driven by hyperphagia. To test whether global expression of the human OGG1 transgene could also confer resistance to weight gain in these mice, the A y /α were crossed with OGG1 Tg mice and selected A y /α Tg [122]. Even though there were trends for increased food intake in the A y /α Tg versus the A y /α, both weight and fat mass were significantly decreased in A y /α Tg males and females.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Subsequent challenging with pollen extract intranasally resulted in a significantly lower allergic inflammatory response in the OGG1 siRNA treated mice compared to the mice receiving control siRNA. Moreover, Ogg1 -/- mice exhibited metabolic disorders (Komakula et al , 2018; Sampath & Lloyd, 2019; Sampath et al , 2012a; Burchat et al , 2021), which has been shown to be an important comorbidity with asthma (Peters et al , 2018; Miethe et al , 2020; Mohan et al , 2019).…”
Section: Introductionmentioning
confidence: 99%